New viewpoint about the effects of boric acid on luminous intensity of Sr2MgSi2O7: Eu, Dy. (10th May 2019) - Zhou, Ziliang; Wang, Dong; Zhang, Xiaoying; Wei, Lai; Yang, Weiguang; Xia, Chuanhui; Liu, Miao; Zhou, Mu; Zhou, Ping; Tian, Song; Tong, Yanqiu; Li, Li; et al.
Abstract: In this work, high temperature solid phase method was applied to prepare Sr2 MgSi2 O7 :Eu, Dy blue light long-persistence materials with different contents of H3 BO3 . Under the condition of low H3 BO3 content, it was difficult for Eu and Dy to enter Sr2 MgSi2 O7 lattice, impurity phase of Sr3 MgSi2 O8 was observed, and initial afterglow luminance of the sample was very low. With the increase of H3 BO3, Sr3 MgSi2 O8 phase disappeared, Eu and Dy entered Sr2 MgSi2 O7 lattice smoothly, and the grain size as well as initial afterglow luminance of samples increased significantly. The initial afterglow luminance of the sample reached the maximum while the H3 BO3 content was 10% (molar ratio). As H3 BO3 content increased further, the initial afterglow luminance reduced rapidly. After detailed analysis, we consider that the key factors influencing the afterglow luminance of samples are the formation and the density of luminous unit, which is greatly determined by the Eu and Dy's entering Sr2 MgSi2 O7 lattice as well as the grain size of Sr2 MgSi2 O7 crystal.